Chinese English as a Foreign Language Teachers’ Immunity and Mindfulness as Predictors of Their Work Engagement - Li, Shengji (Frontiers in Psychology, 2022)
Considering the significant contribution of teachers’ professional triumph in the prosperity of students, the current study aims to investigate the existence of any relationship among three factors influencing teachers’ success: immunity, mindfulness, and engagement. Furthermore, we attempt to investigate whether English as a foreign language (EFL) teachers’ immunity and mindfulness can predict their work engagement. To this end, a Likert-scale questionnaire including items on teacher immunity, mindfulness, and work engagement was distributed to 582 EFL teachers in China through the WeChat application by employing a convenient sampling. To analyze the collected data, the Spearman Rho correlation index and linear multiple regression analysis are employed. The findings are that there does exist an indication of a direct relationship among EFL teachers’ immunity, mindfulness, and work engagement. Also, it is found that immunity and mindfulness can predict EFL teachers’ work engagement. The current study’s findings support the necessity of training language teachers to cope with the EFL context adversities.